Addressing Energy Challenges in Filter Caches - Alves, Ricardo; Nikoleris, Nikos; Kaxiras, Stefanos; Black-Schaffer, David (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2017)
Filter caches and way-predictors are common approaches to improve the efficiency and/or performance of first-level caches. Filter caches use a small L0 to provide more efficient and faster access to a small subset of the data, and work well for programs with high locality. Way-predictors improve efficiency by accessing only the way predicted, which alleviates the need to read all ways in parallel without increasing latency, but hurts performance due to mispredictions.In this work we examine how SRAM layout constraints (h-trees and data mapping inside the cache) affect way-predictors and filter caches. We show that accessing the smaller L0 array can be significantly more energy efficient than attempting to read fewer ways from a larger L1 cache; and that the main source of energy inefficiency in filter caches comes from L0 and L1 misses. We propose a filter cache optimization that shares the tag array between the L0 and the L1, which incurs the overhead of reading the larger tag array on every access, but in return allows us to directly access the correct L1 way on each L0 miss. This optimization does not add any extra latency and counter-intuitively, improves the filter caches overall energy efficiency beyond that of the way-predictor.By combining the low power benefits of a physically smaller L0 with the reduction in miss energy by reading L1 tags upfront in parallel with L0 data, we show that the optimized filter cache reduces the dynamic cache energy compared to a traditional filter cache by 26% while providing the same performance advantage. Compared to a way-predictor, the optimized cache improves performance by 6% and energy by 2%.